KARAKTERISTIK EK TRAK KULIT KAYU MAHONI SEBAGAI BAHAN PEREKAT KAYU - Adi Santoso; Abdurachman (Jurnal Penelitian Hasil Hutan, 2016)
Currenty, raw and supporting materials for adhesives industry such as NaOH, NH OH and methanol are available 4 in the domestic market, while raw material such as phenol and resorcinol derived from petroleum are reduced significantly, then, the use of raw material from other natural resources, like tannins derived from the tree bark is potentially developed. This paper explores and characterizes adhesive raw materials from mahogany bark (Swietenia mahagoni Jacq.) as phenolic source and tapioca as a source of carbohydrates. This paper also studies the copolymerization reaction between mahogany tannin extract with formaldehyde, as well as their mixtures with tapioca for adhesive application and its gluing quality. Pieces of mahogany barks were cut into chips measuring of approximately 2 x 1 x 0.1 cm, then soaked in o an extractor containing of hot water (70-80 C) with a ratio of bark chips : water = 1: 3. Extraction was undergone for three hours with continuous stirring before the mixture was cooled and filtered. The chip bark residue was repeatedly extracted using the same procedure for the second cycle. The obtained filtrates were then mixed with the first one and divided into two parts: crystallized in a water bath and the other part was used for adhesive manufacture. The results showeed that tannin extracted from the bark of mahogany was a dark reddish brown in colour similar with that of phenolic compounds with viscosity of 1.04 poise, specific gravity of 1.02 and the degree of acidity (pH) of 4.0. Extraction of mahogany bark yielded 8.10 % extract, with an average solid content of 2.01%, phenolic compounds level of 6,9%, and distribution of molecular weights ranging from 44-658. The optimum adhesive formulation of the extract mahogany bark was the mixture using of 0.25 mol of technical resorcinol with 15% tapioca, 1 mol technical formalin and 4% catalyst (NaOH 40%) of the total adhesive weight.